Respuesta :
Answer:
[tex]=x^3-x^2-30x+72[/tex]
Step-by-step explanation:
Distribute parentheses:
[tex]=xx^2+x\left(-7x\right)+x\cdot \:12+6x^2+6\left(-7x\right)+6\cdot \:12[/tex]
Apply minus - plus rule:
[tex]=x^2x-7xx+12x+6x^2-6\cdot \:7x+6\cdot \:12[/tex]
Simplified:
[tex]=x^3-x^2-30x+72[/tex]
Its complicated but..
Step-by-step explanation:
( x + 6 ) ( x^2 - 7x + 12 )
x ( x^2 - 7x + 12) + 6 ( x^2 - 7x + 12 )
x^3 - 7x^2 + 12x + 6x^2 - 42x + 72
x^3 + 6x^2 + 12x - 42x - 7x^2 + 72
19x - 49x + 72
30x + 72
x = 72/30
x = 2.4